2007
DOI: 10.1007/s11299-007-0043-5
|View full text |Cite
|
Sign up to set email alerts
|

Refusing to budge: a confirmatory bias in decision making?

Abstract: Confirmatory bias, Rationality, Judgment, Heuristics, Tax policy,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
1
8
0
2
Order By: Relevance
“…Also, confirmation heuristics has a significant negative effect on speculative buying behavior. The results concur with studies of Kosnik (2008), Bashir, Javed, Meer andNaseern (2013) andKahneman (2013). A reasonable explanation is that this study focuses on speculative buying behavior while those previous studies concentrate on judgment and decision making in general.…”
Section: Results Of the Estimated Pls Structural Modelsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, confirmation heuristics has a significant negative effect on speculative buying behavior. The results concur with studies of Kosnik (2008), Bashir, Javed, Meer andNaseern (2013) andKahneman (2013). A reasonable explanation is that this study focuses on speculative buying behavior while those previous studies concentrate on judgment and decision making in general.…”
Section: Results Of the Estimated Pls Structural Modelsupporting
confidence: 92%
“…The study indicated that people tend to believe false hypotheses, despite receiving a tremendous amount of information that contradicts such beliefs. Kosnik (2008) tested for the existence of the confirmation heuristic in different tax policy situations and found that the confirmation heuristic not only exists strongly but also affects decision-making. Unfortunately, there is a lack of studies on the relationship between the confirmation heuristic and speculation behavior.…”
Section: Confirmationmentioning
confidence: 99%
“…El efecto de un mensaje puede ser despreciable en el caso de que no consiga actualizar las actitudes ya existentes. Este es un problema que en el seno de la psicología se ha trabajado como el sesgo de opinión (confi rmatory bias) que sugiere que la mayoría de los individuos no utilizan la nueva información para revisar sus creencias, sino que interpretan esa información a partir de las viejas creencias (Kosnik, 2008). Unos años después, Druckman y Nelson (2003) relativizaron aún más los efectos de los mensajes de la élite política, demostrando experimentalmente que las conversaciones entre los participantes podían disminuir la infl uencia de los framing.…”
Section: De Los Participantes En La Deliberación?unclassified
“…Justo después de la deliberación los cambios a los que asistimos son muy notables, pero seis meses después dichos cambios se relativizan. Una tesis de trabajo habitual dentro de la psicología es el denominado sesgo de opinión (Kosnik, 2008), que ya vimos cómo la ciencia política lo había analizado dentro del estudio de los efectos de los mensajes políticos (framing effects). Aceptar esta tesis tiene consecuencias cruciales para la deliberación porque, en última instancia, vendría a defender que los individuos registran la nueva información solo para re-pensar las alternativas existentes, pero no para modifi car sus creencias.…”
Section: La Encuesta Deliberativa Y La Red Actitudinalunclassified
“…Speaking with friends normalised excessive weight gain during pregnancy. The information relating to drinking caffeinated tea that she had received via her family culture is an example of confirmatory bias (Kosnik, 2007) (affirming what she would like to do -drink caffeinated tea).…”
Section: There's Help and There's 'Help'mentioning
confidence: 99%